2015
DOI: 10.1007/s40291-015-0146-3
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Non-Genetic Determinants of Circulating Levels of Adiponectin in a Cohort of Chilean Subjects

Abstract: Lower adiponectin levels were related to gender, abdominal obesity, physical activity and insulin resistance and were less influenced by the polymorphisms studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
(52 reference statements)
1
5
0
Order By: Relevance
“…Lanas et al (2015) performed a study on a population of 108 adult patients, divided into four groups of 27 people depending on sex and obesity. The relationship of adiponectin and both clinical and genetic factors was studied.…”
Section: Adiponectin -The Adipokine Of Special Rolementioning
confidence: 99%
“…Lanas et al (2015) performed a study on a population of 108 adult patients, divided into four groups of 27 people depending on sex and obesity. The relationship of adiponectin and both clinical and genetic factors was studied.…”
Section: Adiponectin -The Adipokine Of Special Rolementioning
confidence: 99%
“…1. A total of 99 studies on the associations between the polymorphisms in ADIPOQ and the circulating levels of adiponectin and/or lipids were identified [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. The details of the 99 studies enrolled in the meta-analysis are shown in table S1.…”
Section: Literature Search and Details Of The Enrolled Studiesmentioning
confidence: 99%
“…Sixty-one studies [21,24,26,27,[29][30][31][32][33] presented adiponectin and/or lipid data of the subjects with different genotypes of the rs2241766 polymorphism, among them 80 comparisons were distinguished according to ethnicity and health condition. A total of 21 361 subjects were included in the 61 studies or in the 80 comparisons, 58.16 % of them had TT genotype, and the rest had GT or GG genotype (table S4).…”
Section: Literature Search and Details Of The Enrolled Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The adiponectin gene polymorphism is given as the cause of changes in the amount of adiponectin mRNA in adipose tissue of some obese subjects on a lowcalorie diet (Clement and Langin, 2007). Lanas et al (2015) performed a study on a population of 108 adult patients, divided into four groups of 27 people depending on sex and obesity. The relationship of adiponectin and both clinical and genetic factors was studied.…”
Section: Adiponectin -The Adipokine Of Special Rolementioning
confidence: 99%